1992
DOI: 10.1111/j.1365-2044.1992.tb02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose amitriptyline in the treatment of chronic pain

Abstract: SummaryThe analgesic esfcacy of amitriptyline 25 mg was compared with placebo in 41 patients with chronic (more than 3 months) nonmalignant pain, using a double-blind randomised multiple-dose 3-week treatment period crossover design. Amitriptyline 25 mg provided significantly greater esfcacy than placebo, with signijicant differences evident within the j r s t week. There was no significant diyerence on mood scores between amitriptyline and placebo. The results suggest that surprisingly low doses of amitriptyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…However, the doses chosen are those used in clinical practice and have been shown to be effective in both organic and functional pain syndromes (24, 7). The pharmacokinetics of the drug are such that steady state was achieved before the various physiologic tests, and drug levels were obtained and used in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the doses chosen are those used in clinical practice and have been shown to be effective in both organic and functional pain syndromes (24, 7). The pharmacokinetics of the drug are such that steady state was achieved before the various physiologic tests, and drug levels were obtained and used in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…38,76,77,85,86] However, the reporting rate in placebo recipients was also high (12 to 62% excluding trials with placebo that mimicked the active agent), 18,76,77,85] Six to 18% of patients withdrew as a result of adverse events related to amitriptyline, [10,38,76,77] Results from one study suggest that the rate of withdrawal may be directly related to dose; withdrawal rates of 0, 7 and II %, respectively, were observed in patients receiving amitriptyline 25, 50 and 75 mg/day (fig, 3),1 86 1 Adverse events were deemed to be dose-limiting in 71 % of patients in one study.lIO] 38,76,77,85,86] However, the reporting rate in placebo recipients was also high (12 to 62% excluding trials with placebo that mimicked the active agent), 18,76,77,85] Six to 18% of patients withdrew as a result of adverse events related to amitriptyline, [10,38,76,77] Results from one study suggest that the rate of withdrawal may be directly related to dose; withdrawal rates of 0, 7 and II %, respectively, were observed in patients receiving amitriptyline 25, 50 and 75 mg/day (fig, 3),1 86 1 Adverse events were deemed to be dose-limiting in 71 % of patients in one study.lIO]…”
Section: Tolerabilitymentioning
confidence: 99%
“…It was thought that they reduced depression, which in turn reduced pain [8]. Subsequent animal, and later human, models demonstrated that antinociceptive effects could be achieved with relatively small doses of TCAs, even in the absence of clinical depression [9,10]. Therefore, other explanations had to be rendered for their analgesic effects.…”
Section: Basis Of Use Of Antidepressants For Pain: Mechanisms Of Actionmentioning
confidence: 96%